2020
DOI: 10.2147/ott.s279024
|View full text |Cite
|
Sign up to set email alerts
|

<p>Cytochrome C Oxidase Assembly Factor 1 Homolog Predicts Poor Prognosis and Promotes Cell Proliferation in Colorectal Cancer by Regulating PI3K/AKT Signaling</p>

Abstract: Purpose Colorectal cancer (CRC) is one of the most common malignancies in the world. The prognosis of advanced CRC is still poor. The purpose of this study was to identify a gene expression profile associated with CRC that may contribute to the early diagnosis of CRC and improve patient prognosis. Patients and Methods Five pairs of CRC tissues and paracancerous tissues were used to identify causative genes using microarray assays. The prognostic value of Cytochrome C Ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Accumulating evidence has revealed that the upregulated expression of NCAPG is associated with several types of malignant tumor, including gastric cancer ( 6 7 ), HCC ( 9 ) and ovarian cancer ( 10 ). The results of the current study demonstrated that the expression levels of NCAPG were upregulated in CRC tissues and cell lines, which is consistent with the findings of our previous study ( 11 ). In another previous study, upregulated NCAPG expression was found to be associated with TNM stage, distant metastasis, nodal status and vascular invasion in gastric cancer ( 6 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Accumulating evidence has revealed that the upregulated expression of NCAPG is associated with several types of malignant tumor, including gastric cancer ( 6 7 ), HCC ( 9 ) and ovarian cancer ( 10 ). The results of the current study demonstrated that the expression levels of NCAPG were upregulated in CRC tissues and cell lines, which is consistent with the findings of our previous study ( 11 ). In another previous study, upregulated NCAPG expression was found to be associated with TNM stage, distant metastasis, nodal status and vascular invasion in gastric cancer ( 6 ).…”
Section: Discussionsupporting
confidence: 93%
“…Over the past few years, an accumulating number of studies have reported that NCAPG is involved in the pathogenesis of various types of cancer, including breast ( 5 ), gastric ( 6 , 7 ) and prostate cancer ( 8 ), hepatocellular carcinoma (HCC) ( 9 ) and ovarian cancer ( 10 ). In our previous study, gene microarray analysis revealed that the expression levels of NCAPG were upregulated in CRC specimens ( 11 ). However, to the best of our knowledge, the biological functions and clinical implications of NCAPG in CRC remain to be determined.…”
Section: Introductionmentioning
confidence: 96%
“…Although the cancer-based study of COA4, a mediator protein in the assembly process of the cytochrome c oxidase complex ( Watson & McStay, 2020 ), is lacking, overexpression of its related protein (COA1) has also been shown in colorectal cancer. The microarray assay showed that overexpression of COA1 in colorectal cancer tissues is associated with poor prognosis, and suppression of COA1 expression reduces the growth of colorectal cancer cell lines ( Xue et al, 2020 ). Here, we showed that natural peptides from T. stans inhibited the growth, migration and invasion of A549 cells by suppressing the expression of cancer-promoting proteins (NCBP2, AMD, MER34, ENC1, and COA4).…”
Section: Discussionmentioning
confidence: 99%
“…While specific genetic changes in mammalian species lead to cancer resistance (Tollis et al, 2019; Vazquez et al, 2018), the reasons for lower cancer incidence in birds compared to mammals are mostly unexplored (Møller et al, 2017). Interestingly, the COA1/MITRAC15 gene is an oncogene with a role in colorectal cancer (Xue et al, 2020), and its loss could reduce cancer risk. Silencing of COA1/MITRAC15 by miRNAs strongly suppresses Giant cell tumors of the bone (Fellenberg et al, 2016; Herr et al, 2017).…”
Section: Discussionmentioning
confidence: 99%